OP56 Evaluation of the implementation of a complex intervention (babyClear©) to promote increased smoking cessation rates among pregnant women. (13th September 2016) - Bell, R; Glinianaia, SV; van der Waal, Z; Close, A; Rushton, S; Moloney, E; Vale, L; Milne, E; Jones, S; Hamilton, S; Shucksmith, J; Araujo-Soares, V; et al.
Abstract : Background: Rates of smoking at delivery are higher in the North East than in the rest of England (21% vs 13% in 2011/12). The babyClear© approach was commissioned in 2012/13 to support the full implementation of NICE guidance, and rolled out to all localities in the North East. The intervention package included training for staff in maternity and stop smoking services (SSS) and a new referral pathway for pregnant smokers. Systematic identification of smokers and opt-out referral to SSS, with intensive follow up, was emphasised. We aimed to evaluate its impact on referral rates, quit rates and birthweight, and estimate its cost-effectiveness. Methods: Data from all maternity units in the north east of England for deliveries between Jan 2013 and Sept 2014 were linked with SSS referral data. We used a mixed-effects modelling approach to analyse the effect of the intervention on referral to SSS and on the probability of quitting smoking before delivery, using a before and after design. We used a linear mixed-effects model to investigate the impact of quitting during pregnancy on birthweight. Costs of delivering the intervention over five years were estimated. Results: 37, 726 singleton deliveries, including 10, 594 smokers, were analysed. Referrals to SSS increased by 2.5 fold (95% CI 2.2–2.8) by month four after implementation. The odds of quitting during pregnancy nearly doubled (adjusted OR 1.8, 95% CI 1.5–2.2). Quit rates were higher in women who were referred to SSS (aOR 3.2, 95% CI 3.0–3.7) or who set a quit date (aOR 4.2, 95% CI 3.5–4.9). Quit rates were lower among women living in deprived areas (aOR 0.5, 95% CI 0.4–0.6). Birthweight was 6.5% (95% CI 5.8%–7.2%) higher among babies of women who quit during pregnancy compared with those who continued smoking, equivalent to 200 g increase for a reference term birth. Quitters' babies were slightly lighter than babies of non smokers (1.4%, 95% CI 0.1–1.9%; 46 g lower for reference birth). 30 pregnant women (9 pregnant smokers) needed to be treated for each additional quit, at an estimated additional cost of £57 to £938 per quit. Conclusion: Implementation of a system wide intervention to promote smoking cessation in pregnancy, focussed on systematic identification of pregnant smokers and opt-out referral to SSS, substantially increased quit rates, improved birth weight among pregnant quitters and was highly cost effective.